Impact response of straight and curved beams subjected to mid-span impact - Phoon, Kum Weng. (2010)
This dissertation aims to discuss the dynamic behavior of a beam when it is subjected to impact load on the mid-span along its length. To simplify the analysis, the beam studied will be of rectangular cross section; the striking body has a spherical contact surface on the beam. Hertz Theory of impact is assumed to be applicable. Transverse shear effect, rotary